High Ki67 proliferation index but not cell-of-origin subtypes is associated with shorter overall survival in diffuse large B-cell lymphoma - Zaiem, Feras; Jerbi, Rada; Albanyan, Omar; Puccio, Jordyn; Kafri, Zyad; Yang, Jay; Gabali, Ali M (Avicenna Journal of Medicine, 2020)
Background: CD10, BCL6, and MUM1 are commonly used immunohistochemical stains for classifying diffuse large B-cell lymphoma (DLBCL), which is useful in predicting outcome. Conflicting reports of the prognostic value of other markers such as BCL2, CD23, and Ki67 proliferation index have been reported. Our objective was to correlate these immunostains and Hans classification with response to therapy and overall survival. Materials and Methods: A retrospective study of patients diagnosed with DLBCL from 2008–2014 at a tertiary-care cancer hospital. The slides with the IHC stains were reviewed by two independent pathologists. The clinical outcomes––assessed independently––were response to therapy and overall survival. The treatment response evaluation was based on the new Lugano classification. Statistical analyses were conducted using the Fisher’s exact test and Kaplan–Meier survival curves. Significance was set at P < 0.05. Results: Forty-one patients were included in the study with a known Hans classification, available clinical data, and at least 5-year follow-up. CD10 immunostain was reported in all patients, whereas CD23 was the least reported in only four patients. No significant association was observed between CD10, BCL6, MUM1, BCL2, and both Response to therapy and overall survival. Owing to few cases reported CD23 immunostain, further analysis of association is not reported. High Ki67 proliferative index of >80% was statistically significantly associated with shorter overall survival and not statistically significant associated with no response to therapy. Hans classification subtypes were not predictive in regard to therapy response. Conclusion: High Ki67 expression (>80%) was associated with shorter overall survival in DLBCL. Hans classification subtypes were not predictive.
Keywords: Activated B-cell (ABC); BCL2; BCL6; B-lymphocytes; CD10; CD23; cell-of-origin classification; diffuse large B-cell lymphoma (DLBCL); germinal center B-cell (GCB); immunohistochemistry; Ki67; MUM1; overall survival; therapy response